Strategies for Addressing Malnutrition in Toddlers in Rural Areas: A Qualitative Study Review - Firayani, Firayani (Journal Nutrizione, 2025)
The problem of malnutrition in children under five in rural areas remains a complex public health challenge, influenced by low nutritional literacy, limited health infrastructure, family economic conditions, and suboptimal government intervention. This study used a qualitative literature review method, with purposive sampling of national journal articles and health institution reports over the past five years. Content analysis was conducted to identify strategies for nutrition education, utilization of local foods, community-based approaches, and multi-sector synergy. The results of the study indicate that nutrition education for mothers of toddlers plays a key role in improving understanding and practice of breastfeeding and complementary feeding. In addition, strengthening integrated health posts, empowering family economies, and utilizing local foods such as sweet potatoes and moringa leaves increase nutritional resilience. Participatory intervention strategies—involving cadres, local figures, and ongoing monitoring mechanisms—show higher effectiveness than top-down models. Cross-sector collaboration strengthens program implementation and ensures sustainability. Overall, the best strategies to overcome malnutrition are holistic, contextual, and sustainable. This study recommends strengthening community-based approaches, routine monitoring at the village level, and policies that support integration between nutrition education, local foods, and family economic empowerment.